Low Dose of Direct Oral Anticoagulants after Left Atrial Appendage Occlusion - Pedro Luis Cepas-Guillen (MDPI AG, 2021)
The optimal antithrombotic strategy following left atrial appendage occlusion (LAAO) is not yet clearly established. Low-dose non-vitamin K antagonist oral anticoagulants (NOAC) might represent a valid alternative, but data regarding their usage is scarce. The aim of this study was to examine the efficacy and safety of low-dose NOAC compared to single (SAPT) or dual antiplatelet therapies (DAPT) after LAAO. We included consecutive patients with non-valvular atrial fibrillation who underwent LAAO and received low-dose apixaban, SAPT, or DAPT at discharge. The primary objective of this study included an efficacy endpoint (thromboembolic events and device related thrombosis (DRT)) and a safety endpoint (incidence of major bleeding) within the first three months after LAAO. A total of 139 patients were included. This group involved SAPT in 26 (18%), DAPT in 73 (53%), and apixaban in 40 (29%) patients. Follow-up at three-months showed no significant differences in the primary efficacy endpoint (2 (8%) SAPT, 3 (4%) DAPT and 0 (0%) apixaban; p value = 0.25). In contrast, the primary safety endpoint occurred more frequently in DAPT patients (7 (10%) DAPT, 0 (0%), SAPT and 0 with apixaban; p value = 0.03). Combining both efficacy and safety outcomes, low dose apixaban had a lower rate of events (2 (8%) with SAPT, 9 (12%) with DAPT and 0 (0%) with apixaban; p = 0.046). Low-dose apixaban after LAAO may be a valid alternative to DAPT and SAPT as depicted by the reduction in the occurrence of major bleedings and combined DRT/major bleedings respectively. Randomized data will be necessary to validate this strategy.